Analysing meritocratic (in)equality in Singapore: ideology, curriculum and reproduction. Issue 2 (3rd May 2016) - Lim, Leonel
Abstract : In this article I first discuss how in Singapore the concept of meritocracy captures both elitist and egalitarian aspirations, and the ways in which its education policies have for a long time vacillated between these conflicting dimensions. I then argue that critical studies of meritocracy need to go beyond an understanding of the term as an inherently unstable concept instantiated problematically in policy and practice. Rather, as I develop the argument further, the dynamics of meritocracy needs to be appreciated as an ideology that is negotiated by dominant social groups as these seek to legitimize particular distributions of social resources. Such dominant ideologies, however, are not only produced in the education system; they are also reproduced through it, often in far more complex ways. To see how these ideologies and their tensions animate the very mechanism that sits at the centre of the reproduction of (in)equality, viz. the curriculum, the rest of the article provides an account of how one particular subject area is differently taught in an elite and a mainstream school.